Obstacles and Development Strategies in Improving Qur’anic Reading Skills among Junior High School Students in a Pesantren Context - Surmiyanti; Imam Asfali; Fadhilah Zuhriyah; Ahmad Harisul Fikri; Sumaryati; Siti Farhah A. Aziz (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
This research is motivated by the persistence of variations in junior high school students' ability to read the Qur’an, particularly in fluency, accuracy in makharij al-letters, application of tajweed, and consistency of practice. This research aims to analyze the main obstacles students face in developing the ability to read the Qur’an and to formulate contextual and applicable development strategies in the pesantren environment. The research uses a qualitative case study design. Data were collected through observation of Qur’an learning, in-depth interviews with caregivers and coaches, ustaz and ustazah, and students, and review of learning documents, including schedules, achievement targets, and evaluation notes. The data is analyzed thematically through the stages of data reduction, coding, theme development, and a conclusion is drawn. The results showed that student obstacles included differences in initial ability, limited time for independent practice, fluctuating motivation for learning, and uneven individual feedback over time. Development strategies considered adequate include early ability mapping, gradual learning based on talaqqi and tashih, structured murajaah habituation, increased mentoring intensity, and periodic evaluation against achievement indicators. These findings contribute as a basis for improving the Qur’an Reading coaching program in pesantren-based junior high schools to be more measurable, consistent, and sustainable.